A Case of Traumatic Proptosis. (7th March 2013) - Desai, Bobby
Abstract : We present a case of traumatic proptosis in a competitive football player. This entity can occur with a significant decrease in vision, but in this case it did not. Some other causes of this condition are also discussed. A review of some traumatic conditions that may cause proptosis is provided as well.